THE PERFORMANCE TESTING OF JAVA VOICE MESSENGER APPLICATION ON LOCAL AREA NETWORK - Tri Handayani (Widyariset, 2012)
Java Voice Messenger application was developed by Java technology Standard Edition (J2SE). This application intend to facilitates communication among user on Local Area Network. They did not need the internet connection and it can perform voice file transfer process. This application can send right voice message and sound quality after compression still have a fairly good quality, and distortions can be ignored. In performance testing, delay produced quite large because the process of sending and receiving on one computer at the same time, but it depends on the size of a sound file. In addition, delay can also be affected by distance and physical media. Sustainability of communication can be maintained even if there is damage or loss of some packets at the time of delivery.